Identification of Factors Contributing to Primary Female Subfertility by Diagnostic Hystero-Laparoscopy: An Experience of Private Hospital - Yousaf Latif Khan; Sajida Imran; Zahra Samreen (Shalamar Medical & Dental College, Lahore, Pakistan, 2022)
Background: Management of subfertility is influenced by the diagnosis of its causative factor. Combined diagnostic hystero-laparoscopy has emerged as an effective procedure in identifying causative factors of female subfertility. Objectives: This study aimed to identify contributory factors to primary female subfertility by diagnostic hystero-laparoscopy. Methods: This descriptive study was conducted at the Department of Obstetrics and Gynecology of Hameed Latif hospital, Lahore, Pakistan from December 2021 to May 2022. Data was collected from 344 women with female primary subfertility, undergoing combined diagnostic hystero-laparascopy. All the demographic data along with identified causative factors (tubal blockade, cervical Os stenosis, endometrial polyp, uterine septum, uterine fibroid, endometriosis, peri tubal adhesions and polycystic ovaries) during the procedure were recorded in predesigned study proforma. Data were analyzed through SPSS software 23. Results: Mean age of the patients was 25±5.0 years and the mean duration of subfertility was 3.8+0.55 years. Two hundred and eighty-four (82.56%) patients had abnormal findings, while sixty (17.44%) had normal findings. Out of 284 patients, 94(34%) had one identified factor, while 190 (66%) patients had two or more identified factors for primary subfertility. Polycystic ovaries were seen in 128(37.21%) patients, followed by tubal blockade in 81(23.54%), peri tubal adhesions/hydrosalpinx in 58(16.86%) patients. Conclusions: Diagnostic hystero-laparoscopy is an effective diagnostic procedure for the evaluation of female factor subfertility and may be helpful to gynecologists in devising further management plans.